The implementation of family‐focused practice in adult mental health services: A systematic review exploring the influence of practitioner and workplace factors. (1st April 2021) - Gregg, Lynsey; Adderley, Hope; Calam, Rachel; Wittkowski, Anja
Abstract: There is increased recognition of the need for greater and more appropriate support to be offered to families in which a parent experiences mental illness and has dependent children. One way of meeting this need is for adult mental health services to take a more family‐focused approach. However, there are recognized difficulties in facilitating family‐focused practice (FFP). The current review systematically synthesized quantitative and qualitative literature of practitioner perspectives and experiences of FFP in adult mental health settings to identify modifiable factors associated with its successful implementation. Five databases were searched systematically leading to the inclusion and quality assessment of 19 papers, ten of which were quantitative and nine qualitative. Analysis was guided by a narrative synthesis approach. Factors shown to influence FFP functioned at both practitioner and workplace levels and included personal attitudes, beliefs about job role, and perceptions of workplace support. Practitioners who felt that a family‐focussed approach was inappropriate or detrimental to service users or outside of their remit as mental health professionals were less likely to adopt this approach. For those who saw the potential benefits of FFP, lack of confidence in their ability to deliver such an approach and lack of training can be barriers, as can lack of support and resources within services. This review highlights the need for actions to boost the awareness of adult mental health practitioners working with parents and to increase their confidence. It also makes the case for broader organizational support if family‐focussed practice is to be implemented successfully.